Cybercrime in the pandemic digital age and beyond - Smith, Russell G. (Palgrave studies in cybercrime and cybersecurity, 2023)
“The editors of this book have assembled an all-star cast of prominent academics working in the field of cybercrime to explore the different crime challenges posed by Covid to provide both facts and wisdom. For those who practice, or make policy, or are just interested, this is a must-read book.” -Professor David S. Wall, University of Leeds, United Kingdom “This book is a timely addition to the literature on the various cybercriminal risks and mitigation solutions during the trying times surrounding the coronavirus pandemic. It provides directions that should be considered so as to avoid malicious cyber activities that may occur in any future pandemics.” -Professor Kim-Kwang Raymond Choo, University of Texas at San Antonio, USA “Combining empirical engagement and socio-legal thinking, this book makes an insightful contribution to the literature on cybercrime during a time of crisis and forces us to think about some of the challenges and opportunities ahead.” -Associate Professor Anita Lavorgna, University of Bologna, Italy This edited collection presents current research dealing with crime involving information and communications technologies in the months immediately before, during and following the coronavirus pandemic since 2019. Information and communications technologies played a pivotal role during the pandemic in communicating information across the globe on the risks and responses to the pandemic but also in providing opportunities for various forms of illegality. This volume describes the nature and extent of such illegality, its connection to the pandemic and how digital technologies can assist in solving not only the health crisis but also the associated crime problems. It identifies technological solutions to cybercrime, legislative responses, crime prevention initiatives and policy discussions dealing with the most critical issues present during and following the pandemic. Russell G Smith is Professor at Flinders University, South Australia. Rick Sarre is Emeritus Professor at the University of South Australia. Lennon Yao-Chung Chang is Associate Professor at Deakin University, Australia. Laurie Lau is Chairman at the Asia Pacific Association of Technology and Society, Hong Kong. .